Om behovet att skilja mellan empiriska och begreppligt konstitutiva frågor - Schaffar, Birgit (Studier i Pædagogisk Filosofi, 2012)
This article clarifies the fundamental difference between empirical and conceptual questions in education. In the ongoing debate about the role of philosophy of education, many authors either unreflectively assume or actively demand that philosophy of education should try to adapt to (empircal) science. Through a discussion of the possibilities of a child to open up to educational processes (Herbart: Bildbarkeit) the article illustrates how philosophical reflection on education fundamentally differs in character from empirical approaches. It suggests that one important task for philosophy of education is to clarify what questions can be answered empirically from those that are constitutive of our understanding of education. Wittgenstein’s later philosophy is used as a central starting point in this article.